Do health education initiatives assist socioeconomically disadvantaged populations? A systematic review and meta-analyses - E. L. Karran; A. R. Grant; H. Lee; S. J. Kamper; C. M. Williams; L. K. Wiles; R. Shala; C. V. Poddar; T. Astill; G. L. Moseley (BMC, 2023)
Abstract Background Health education interventions are considered critical for the prevention and management of conditions of public health concern. Although the burden of these conditions is often greatest in socio-economically disadvantaged populations, the effectiveness of interventions that target these groups is unknown. We aimed to identify and synthesize evidence of the effectiveness of health-related educational interventions in adult disadvantaged populations. Methods We pre-registered the study on Open Science Framework https://osf.io/ek5yg/ . We searched Medline, Embase, Emcare, and the Cochrane Register from inception to 5/04/2022 to identify studies evaluating the effectiveness of health-related educational interventions delivered to adults in socio-economically disadvantaged populations. Our primary outcome was health related behaviour and our secondary outcome was a relevant biomarker. Two reviewers screened studies, extracted data and evaluated risk of bias. Our synthesis strategy involved random-effects meta-analyses and vote-counting. Results We identified 8618 unique records, 96 met our criteria for inclusion - involving more than 57,000 participants from 22 countries. All studies had high or unclear risk of bias. For our primary outcome of behaviour, meta-analyses found a standardised mean effect of education on physical activity of 0.05 (95% confidence interval (CI) = -0.09-0.19), (5 studies, n = 1330) and on cancer screening of 0.29 (95% CI = 0.05-0.52), (5 studies, n = 2388). Considerable statistical heterogeneity was present. Sixty-seven of 81 studies with behavioural outcomes had point estimates favouring the intervention (83% (95% CI = 73%-90%), p < 0.001); 21 of 28 studies with biomarker outcomes showed benefit (75% (95%CI = 56%-88%), p = 0.002). When effectiveness was determined based on conclusions in the included studies, 47% of interventions were effective on behavioural outcomes, and 27% on biomarkers. Conclusions Evidence does not demonstrate consistent, positive impacts of educational interventions on health behaviours or biomarkers in socio-economically disadvantaged populations. Continued investment in targeted approaches, coinciding with development of greater understanding of factors determining successful implementation and evaluation, are important to reduce inequalities in health.